Materialität und Präsenz spätantiker Inschriften. Eine Studie zum Wandel der Inschriftenkultur in den italienischen Provinzen - Bolle, Katharina (Materiale Textkulturen, 2020)
That inscriptions are not only texts but also material objects of specific materiality and presence is one of the recent central insights of ancient epigraphy. This understanding is applied here for the first time systematically, across different regions and over an entire epoch, by examining the change in the inscriptions culture in late antiquity with a view of the Italian peninsula.